LADM extensions to maritime domain in multi-register environment - Case study Croatia. (March 2021) - Flego, Veljko; Roić, Miodrag; Benasić, Irena
Highlights: Multi-register environment relies on registration of features in several registers. Redundant data in registers and cross-registration are common. Maritime domain in Croatia has a specific ownership status. Relations between registers have a distinct pattern. Introducing of new model classes can help in modeling of relations between registers. Abstract: Traditional land administration key registers are established for the onshore area and after been developed and technologically improved during many decades, nowadays they are in a stable and mature evolution phase. Registers covering the administration of offshore spaces, i.e. the maritime domain, are usually extended from onshore registers or developed for a single purpose, creating a multi-register environment with many administration challenges and issues caused by many actors involved and by complex registration processes. In this paper, an analysis of maritime domain registration in Croatia has been performed by using Unified Modeling Language class models. The analysis includes two close connected key land registers, Cadastre and Land book, as well as: other authoritative data from Territorial units/Address register; Utility cadastre; Register of concessions on maritime domain; spatial plans, and a series of registers dedicated to natural resources exploitation, nature and cultural heritage protection. Redundant data and cross-registration is present in all basic Land Administration Domain Model (LADM) classes contained in the registers, as well as 3D overlapping of spatial extent of registered spaces and tenure. The basic LADM classes were semantically identified in class diagrams of registers and compared to LADM using a schema matching methodology on the object level, with emphasis on required registration in different registers. Shared classes were identified and a possible upgrade and extension of the current model is proposed to facilitate the registration process.